Association between Chlamydia trachomatis antibodies and subfertility in the Northern Finland Birth Cohort 1966 (NFBC 1966), at the age of 31 years - KARINEN, L.; POUTA, A.; HARTIKAINEN, A.-L.; BLOIGU, A.; PALDANIUS, M.; LEINONEN, M.; SAIKKU, P.; JÄRVELIN, M.-R. (Epidemiology and Infection, 2004)
The objective of this study was to assess the serological association between previous Chlamydia trachomatis infection and subfertility in a general population sample. A nested case ( n =493)-control ( n =986) study in a population-based birth cohort consisting of 12058 live births from the year 1966 was conducted. The analysis was restricted to those 6007 cohort members who replied to a postal inquiry and participated in a health examination including blood samples at the age of 31 years. The presence of C. trachomatis -specific serum IgG antibodies was screened by a synthetic peptide-based enzyme-linked immunosorbent assay. All the positive sera were further tested by the microimmunofluorescence method using immunotype pools and individual immunotypes of C. trachomatis as antigens. An association was found between the detection of immunotype-specific C. trachomatis antibodies and subfertility both in men and women. The results of the present study confirm the serological association between past C. trachomatis infections and subfertility in male or female partners of the couple in the population-based sample.